A inovação pedagógica nos (entre)laçamentos curriculares da Escola Municipal de Educação Infantil Zezé Tavares - Rorato, Adriana (2019)
This master thesis is the result of a theoretical-practical investigation whose main objective was to investigate the challenges and possibilities that cross the (re) invention curricular movements in a School of Early Childhood Education. The work starts from critical theorization about the production of curricular thinking in dialogue with authors like Moreira and Silva (1995) and Lopes and Macedo (2010; 2011), referring the discussions on the field of Early Childhood Education as a political, collective, plural, producer of meanings whose expansion, qualification and recognition are still forming. The elements brought to the discussion have a critical epistemological basis and emerged from research with a qualitative approach, developed with Zezé Tavares Municipal School of Infantile Education in the city of Bagé / RS as the investigative locus. The construction of data was based on the dialogues and productions of 10 (ten) subjects representative of the segments of teachers, employees, and managers of the school and the results of the work were analyzed through discursive textual analysis, evidenced from the construction of structural networks with Atlas.ti software. The research findings were organized based on such networks and the theoretical framework of the field of Early Childhood Education, especially the reading of Barbosa (2013, 2009), Fochi (2015) and Richter and Barbosa (2010). The arrangement of this analysis was interwoven into three sections, intentionally articulated in an intertextualisation from the emancipatory pedagogical innovation as a possibility for (curricular) invention in the Early Childhood Education. Finally, considerations have presented that point out the possibilities of innovation in everyday movements as a way of promoting the growth and cultural enrichment of the subjects, as well as the (re) signification of space-time, materialities and curricular approaches in Early Childhood Education.